A multi‐institutional assessment of a short‐form personality questionnaire for use with macaques. Issue 5 (2nd September 2018) - Hopper, Lydia M.; Cronin, Katherine A.; Ross, Stephen R.
Abstract : There are two commonly‐used methods for calculating primates' personality dimensions, behavioral assessments and surveys, which can be used separately or in conjunction. However, these methods have limitations. Behavioral assessments, such as the novel object test or human intruder test, often require subjects to be separated and demand highly‐controlled conditions. This is likely not feasible in many zoological institutions. Furthermore, it may be difficult to replicate methods across institutions. While surveys are easier to implement, the most commonly used one – the Hominoid Personality Questionnaire (HPQ) – is long and can be time consuming to complete, especially if multiple individuals need assessing. Therefore, we developed a short‐form personality questionnaire for use with macaques. We aimed to retain elements of published scales while creating a tool that would be less time consuming to complete. After creating a novel 26‐item scale (28 fewer items than the HPQ), we gathered ratings for 63 Japanese macaques ( Macaca fuscata ) living in eight zoos accredited by the Association of Zoos and Aquariums. Using principal components analysis, we identified four components to describe the Japanese macaque personality: Openneness, Friendliness, Dominance, and Anxiety/Reactivity. While further testing is required to fully validate this scale, we tested for the convergent validity of our questionnaire by correlating the responses of a subset of the monkeys to a novel object and assessed the face validity of our scale in comparison to previously‐published scales.